Low-carbon cementitious composite incorporated with biochar and recycled fines suitable for 3D printing applications: hydration, shrinkage and early-age performance - Karol Federowicz; Krzysztof Cendrowski; Paweł Sikora (Fracture and Structural Integrity)
In recent years, the construction industry has witnessed significant advancements in concrete technology, particularly with the integration of 3D printing in cement-based materials. While this innovation offers promising opportunities for the sector, the high binder and fine particle content of 3D printing mixes presents a substantial environmental challenge due to their considerable carbon footprint. To mitigate this impact, strategies often involve substituting portions of the binder or aggregate with waste materials. This article presents a comparative analysis of two promising approaches to reducing the carbon footprint of 3D printing concrete mixes by partially replacing cement with biochar and recycled fines. The study examines the effects of these materials on the rheological properties and early-age hydration processes of the 3D printing mix. A reference mix (REF) was established, followed by the development of eight additional mixes, with four incorporating biochar and four incorporating recycled fines, each replacing 1.25%, 2.5%, 5%, and 10% of the cement volume. The findings indicate that recycled fines have a neutral effect on the spread flow diameter of the mixture but increase initial deformations in printed elements. Conversely, biochar, due to its water absorption capacity, reduces fluidity, enhancing buildability by enabling faster printing with minimal initial deformation. Additionally, replacing up to 2.5 vol.% of cement with either material accelerates the normalized heat flow, contributing to a quicker gain in mechanical properties. However, biochar increases shrinkage deformations within the first 12 hours, while recycled fines mitigate them. Importantly, replacing up to 10 vol.% of cement with these materials does not significantly compromise early compressive strength.